1998
DOI: 10.1111/j.1600-0897.1998.tb00369.x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation Effect of Early Pregnancy Factor‐Positive Serum into Bovine In Vitro Fertilization Culture Medium

Abstract: The data suggest that an EPF-like substance(s) may be secreted from the in vitro fertilized bovine ovum but not from the cumulus cell, and that the EPF in the pregnant serum may accelerate the development of the bovine embryo in IVF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Using a mathematical model, Shorten et al [31] demonstrated that if IFNT signaling occurs later than day 13 of the cycle, pregnancy is not recognized irrespective of the IFNT concentration. Other candidate markers are early pregnancy factor (EPF) and EPF-like substances because EPF and EPF-like substances are detected in the serum of pregnant cows and are extraordinarily produced by embryos within 24-48 h after fertilization [32]. Ito et al [32] suggested that these EPFs regulate the maternal immune response to prevent rejection of the allograft fetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a mathematical model, Shorten et al [31] demonstrated that if IFNT signaling occurs later than day 13 of the cycle, pregnancy is not recognized irrespective of the IFNT concentration. Other candidate markers are early pregnancy factor (EPF) and EPF-like substances because EPF and EPF-like substances are detected in the serum of pregnant cows and are extraordinarily produced by embryos within 24-48 h after fertilization [32]. Ito et al [32] suggested that these EPFs regulate the maternal immune response to prevent rejection of the allograft fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Other candidate markers are early pregnancy factor (EPF) and EPF-like substances because EPF and EPF-like substances are detected in the serum of pregnant cows and are extraordinarily produced by embryos within 24-48 h after fertilization [32]. Ito et al [32] suggested that these EPFs regulate the maternal immune response to prevent rejection of the allograft fetus. Additionally, the preimplantation embryo produces TGFβ and insulin-like growth factors I and II in cows [33].…”
Section: Discussionmentioning
confidence: 99%
“…There have been remarkable discrepancies among molecular weights of purified EPF reported by different investigators (ranging from 10 to 21.5 kD), probably due to differences in original materials and isolation procedures. 9,24,38,39 Ito et al 13 insisted that, because Cavanagh and Morton purified EPF from human platelets, it might not be a true EPF. In order to identify true EPF, EPF has to be purified from early-pregnant serum.…”
Section: Discussionmentioning
confidence: 99%
“…EPF may be most useful for the evaluation of embryo quality in the in 6itro fertilization-embryo transfer treatment. 13 Chaperonin 10 (cpn 10) is one of the heat-shock protein (hsp) families, which act in conjunction with cpn 60 to mediate protein folding under the existence of ATP in mitochondria. 14,15 Cpn 60 is composed of two stacked 7-subunit rings with adenosine triphosphate (ATP)ase activity.…”
Section: Introductionmentioning
confidence: 99%
“…was EPF-like substance. 5 EPF in the pregnancy serum has been detected in many animal species, [6][7][8][9] including the Red Deer (Cer6us elaphus). 10 In almost all the animals examined, EPF was detected within 24 -48 hr after mating and it was detected until the second trimester using the rosette inhibition test.…”
Section: Introductionmentioning
confidence: 99%